Synthesis and Antimicrobial Activity of 1-[2-(10-p-Chlorobenzyl) phenothiazinyl]-3-(substituted aryl)-2-propen-1-ones - R. K. Upadhyay; Megha S. Upadhyay; S. Jain (E-Journal of Chemistry)
Aiming at the development of antimicrobial agents, we have synthesized nine chlorobenzyl substituted phenothiazinyl chalcones by condensing 2-acetyl phenothiazine with aldehyde derivatives in dilute ethanolic sodium hydroxide solution at room temperature according to Claisen - Schmidt condensation and subsequent reaction of products with p-chlorobenzyl bromide. Structures of these compounds were elucidated by their IR, 'H NMR spectroscopic data and microonalyses. The antimicrobial activity of the new products was evaluated by Filter Paper Disc Method.